The big big big book of Tashi - Fienberg, Anna.; Fienberg, Barbara; Gamble, Kim (Crows Nest, NSW : Allen & Unwin, 2001)
A collection of fourteen tales which chronicles the adventures of Tashi.
Tashi -- Dragon breath -- Tashi and the giants -- The bandits -- Tashi and the ghosts -- The mountain of white tigers -- Tashi and the genie -- Tashi and the stolen children -- Tashi and the Baba Yaga -- Gone! -- Tashi and the demons -- The magic bell -- Tashi and the big stinker -- The magic flute.
Pub Weekly
4.3
K-3.
K-3
Keywords: Children's stories, Australian; Tashi (Fictitious character) -- Juvenile fiction; Adventure and adventurers -- Fiction; Storytelling -- Fiction; Tashi (Fictitious character) -- Fiction; Adventure fiction; Storytelling -- Fiction; Tashi (Fictional character) -- Fiction